La penumbra como fenómeno espacial compositivo de una poética del espacio arquitectónico (2024)
The concept of penumbra could have a perception of fear or mystery, it is part of the experience of encountering a terrestrial void, a concealment of what is visible, an image of the dark and the unknown.